Etymology of the toponym «Lamgan» (Eurasian Journal of Philology Science and Education, 2024)
In this article, from a linguistic point of view, the name of the Lamgan region, which now belongs to the state of Afghanistan, is considered. The article attempts to determine the true origin of the toponym «Lamgan», since before that there were various unreliable assumptions about the origin of this name. Among them there is also a reflection on the origin of this name of the conqueror of India, the founder of the Mughal dynasty, a descendant of Amir Temir, but known to linguists for his valuable autobiographical work «Baburname», written in the Chagatai language, Zahiriddin Muhammad Babur (1483-1530). According to him, the grave of the Great Lama, the father of the prophet Noah, is located in the Alisheng fog (in the Lamgan region). In some chronicles it is also called Lamech, Lamekan. The inhabitants of this country sometimes pronounce the letter kaf as ghayn. That is why the area was called Lamgan. At first glance, this opinion looks like a scientific etymological version, but in the course of linguistic analysis it turned out that this version is based only on popular beliefs. During the study, collection methods, traditional description, comparative methods were used. As a result of the study, we came to the conclusion that the name Lamgan is based on the name of the Lamba (Lampaka) people who inhabited it, i.e. ethnonym with the addition of the Persian suffix -ğān to it, which has the meaning of belonging (Lam + ğān).Key words: Lamgan, Baburname, Babur, toponym, etymology.